1970
DOI: 10.3329/bjvm.v4i1.1518
|View full text |Cite
|
Sign up to set email alerts
|

Avian Salmonella Infection: Isolation and Identification of Organisms and Histopathological Study

Abstract: The Present study was performed in the Department of Pathology, BAU, Mymensingh during the period from January to December 2004. The study was conducted to determine the occurrence and pathology of pullorum disease, fowl typhoid and salmonellosis (paratyphoid infection) in dead chickens at necropsy in Mymensingh district of Bangladesh. A total of 70 samples (liver, ovary and intestine) were collected for isolation of bacteria in different media, and identification was performed based on the staining, cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
1
2

Year Published

1970
1970
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 3 publications
9
23
1
2
Order By: Relevance
“…It indicated that the 12 (80%) isolates were Salmonella gallinarum and 3 (20%) were Salmonella pullorum. The higher rate of Salmonella gallinarum than S. pullorum is supported by Hossain et al (2006) who detected 62.5% S. gallinarum and 25% S. pullorum.…”
Section: Seroprevalence Studysupporting
confidence: 53%
See 1 more Smart Citation
“…It indicated that the 12 (80%) isolates were Salmonella gallinarum and 3 (20%) were Salmonella pullorum. The higher rate of Salmonella gallinarum than S. pullorum is supported by Hossain et al (2006) who detected 62.5% S. gallinarum and 25% S. pullorum.…”
Section: Seroprevalence Studysupporting
confidence: 53%
“…The prevalence was varied in terms of age (Table 1) Isolation of causal agent A total of 15 (7.5%) Salmonellae were isolated from 200 liver of dead birds of selected flocks of different groups and characterized by using specific biochemical tests and Gram's staining technique ( Table 2). The rate of isolation was slightly lower than Hossain et al (2006) but markedly lower than Islam et al (2006). This may be due to variation of severity.…”
Section: Seroprevalence Studymentioning
confidence: 69%
“…Contudo, quando a replicação não é controlada, a salmonela se replica no baço e fígado acarretando a uma acentuada hepatoesplenomegalia (Chappell et al, 2009). Estudos anteriores apontaram que as alterações macroscópicas do tifo aviário são caracterizadas por aumento do fígado e do baço com áreas de necrose nesses órgãos (Hossain et al, 2006;Ezema;Onuoha;Chah, 2009) e hemorragia no ovário e nas tonsilas cecais (Hossain et al, 2006).…”
Section: Resultsunclassified
“…The disease usually follows the ingestion of food or water contaminated by the excreta of clinically infected birds or carriers but can also be transmitted by attendants through contaminated hands, feet and clothes (Lowry et al, 1999;Berchieri et al, 2001). In the subacute and chronic stages of the disease, the liver and spleen are mostly affected, with multiple white foci, severe swelling and discolouration being observed (Hossain et al, 2006;Shivaprasad & Barrow, 2008).…”
Section: Introductionmentioning
confidence: 99%